Synthesis and Characterization of Boron Trifluoride Doped High Performance Polyaniline - K. Basavaiah; D. Samsonu; A. V. Prasada Rao (E-Journal of Chemistry)
We report simple synthesis of boron trifluoride (BF3) doped defect free high performance polyaniline (HPPANI) in two step method. Firstly, HPPANI was prepared via self-stabilization dispersion polymerization method in a heterogeneous reaction medium. Second step involves doping of emeraldine base form of HPPANI with boron trifluoride under reduced vacuum. The resultants BF3 doped HPPANI have been well characterized by using UV-Visible spectroscopy, Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and thermogravimetry. The spectroscopic data indicated that the interaction between HPPANI and BF3.Thermogravimetry studies revealed that the BF3 doping improved the thermal stability of defects free PANI.